MASKULINISASI IKAN CUPANG (Betta sp.) MENGGUNAKAN EKSTRAK AKAR GINSENG (Panax sp.) - Asrul . Ferdian; Muslim .; Mirna Fitrani (Universitas Sriwijaya, 2017)
ABSTRACT The use of extract root ginseng in the process of Betta fish masculinization is expected to increase the testosterone. The purpose of this research is to determine the effect ginseng root extract to the percentage of the male betta fish by masculinization. This study has been conducted at the Basic Aquaculture Laboratory, Faculty of Agriculture, Sriwijaya University. This study use a completely randomized design with 4 treatments and 3 replications. The treatments in this research was betta fish larvae aged 7 days that submersed on ginseng root extract media with different concentration for 8 hours. The treatment were the addition of ginseng root extract as much as 1 mg/L (P1), 2 mg/L (P2), 3 mg/L (P3), 4 mg/L (P4) and without ginseng root extract addition as control (P0). Parameters observed consist of percentage of betta fish male, survival rate and quality of water. The result of this research shows that the addition of extract panax ginseng with difference concentration has significant effect to male betta fish percentage, but there is no a significant effect on survival rate. Treatment P3 with concentration 3 mg/L is the best result, it produced 95.05% of male betta fish after immersion for 8 hours. Keywords : Betta fish, Ginseng root extract, Immersion, Masculinization